Once upon a time. The complete first season [videorecording (DVD)] - Horowitz, Adam; Kitsis, Eddy (Once upon a time., 2012)
On her 28th birthday, Emma Swan meets Henry, the son she gave up for adoption 10 years ago. Henry believes Emma is the daughter of Snow White and Prince Charming, prophesied to break a powerful curse. Unconvinced, Emma returns Henry to Storybrooke, where she encounters the enigmatic Mr. Gold and clashes with mayor Regina Mills, the boy's adoptive mother, who Henry insists is none other than the Evil Queen!